ANALYSIS OF THE COMPOSITION OF THE CATCH KURAU GILLNET THE USE OF DIFFERENT MESH SIZES IN THE WATERS PURNAMA, DUMAI BARAT DISTRICT, DUMAI CITY, RIAU PROVINCE - Rengi, Pareng; Yani, Alit Hindri; ', Sarwono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted on october 2014 in waters Purnama, Riau Provincethe. The aim of this research was to undertand the difference in species and composition cat fish using kurau gillnet at the mesh sizes 7 inches and 8.This research was using survey method. Using nets kurau done during 5 day. While water quality parameters measured in description.Kurau gillnet catches consisted of 5 species of both the mesh size of 7 inches and 8 with a total weight of 271.8 kg. The type of fish caught is great.T test results showed no difference in the catch on the mesh size of 7 inches and 8. Chi-square test results showed that there was no difference in the composition of the catch in different mesh sizes.Keyword : Kurau gillnet, mesh size 7 inches, 8 inches